2010
DOI: 10.1007/s00296-010-1421-6
|View full text |Cite
|
Sign up to set email alerts
|

Low bone mass in juvenile onset sclerosis systemic: the possible role for 25-hydroxyvitamin D insufficiency

Abstract: Juvenile onset systemic sclerosis (JoSSc) is a rare disease, and there are no studies focusing in bone mineral density and biochemical bone parameters. Ten consecutive patients with JoSSc and 10 controls gender, age, menarche age, and physical activity matched were selected. Clinical data were obtained at the medical visit and chart review. Laboratorial analysis included autoantibodies, 25-hydroxyvitamin D (25OHD), intact parathyroid hormone, calcium, phosphorus, alkaline phosphatase and albumin sera levels. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 32 publications
1
14
0
2
Order By: Relevance
“…Of the five case-control studies, two demonstrated lower 25(OH) D levels in patients with scleroderma than controls(142, 143), and three did not(144-146). In two case-only analyses, it was found that 25(OH)D levels were, not surprisingly, lower in those with more severe underlying scleroderma, more longstanding disease, more disease activity, more pulmonary hypertension and lower diffusing lung capacity(147, 148).…”
Section: Resultsmentioning
confidence: 97%
“…Of the five case-control studies, two demonstrated lower 25(OH) D levels in patients with scleroderma than controls(142, 143), and three did not(144-146). In two case-only analyses, it was found that 25(OH)D levels were, not surprisingly, lower in those with more severe underlying scleroderma, more longstanding disease, more disease activity, more pulmonary hypertension and lower diffusing lung capacity(147, 148).…”
Section: Resultsmentioning
confidence: 97%
“…Many recent articles have tried to clarify the association of low vitamin D levels with bone mineral density (BMD) in SSc and fracture risk in SSc patients, based on the role of vitamin D in calcium-phosphate and bone homeostasis. Overall, decreased bone mineral density (BMD) was reported in the majority of scleroderma patients presenting with low levels of vitamin D (<30 ng/ml) [ 36 – 39 ]. In addition, Shinjo et al identified a high prevalence of 25(OH)D insufficiency in SSc that correlates with hip BMD (femoral neck and total femur) [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several experts agree to define vitamin D deficiency as serum levels below 10 ng/ml [9,10,16,18,22,38]. However, this definition is not universal, with some authors suggesting deficiency levels to be lower than 20 ng/ml (50 nmol/l) [39,41], taking in consideration the regulatory variations of PTH. In turn, vitamin D insufficiency is commonly defined as serum levels between 10 and 30 ng/ml, with levels > 30 ng/ml being considered sufficient [9,22,24,27].…”
Section: Discussionmentioning
confidence: 99%